Evaluasi program perdagangan bangunan untuk keberlanjutan kelayakan kerja di Nigeria - Ibukun Francis Adeagbo; Ibiwumi Abiodun Alade; Olusiji Olaseni Lemo (Universitas Pendidikan Indonesia, 2026)
Building-related programs in technical higher education are expected to equip students with employable skills; however, many graduates have yet to demonstrate adequate technical competence. This article aims to evaluate building-related programs in technical higher education to enhance graduates’ employability, identify existing challenges, and propose solutions to prevent unemployment while sustaining skill-based programs. A survey research design was adopted, involving 1,390 participants. Data were collected using a validated and reliable instrument titled Building Trade Objectives, Content and Sustainability Questionnaire (BTOCSQ). Descriptive statistics were used to analyze the data. Results indicated that program objectives were moderately adequate, sustainability practices were strong, and curriculum content was only slightly adequate. The study concluded that regular updates to program objectives and content are essential to keeping pace with technological advances. Hence, curriculum developers should prioritize periodic reviews of building trade programs to enhance relevance, improve graduate employability, and sustain skills development initiatives.